The central Maghreb's Hadith tellers between the Detective Hadith and the Ingenuity of know, how from the end of conquest until the end of Sixth century AH (12th AD) - mazouz, ayoub (The Algerian Historical Journal, 2026)
The science of hadith established itself among the transmitted sciences in Maghreb. these texts, came to the Maghreb with the early conquests led by prophet companions. Due to the unstable situation and the change in politics and the different aspects of life, their impact could reach the science of hadith and hadith tellers, especially as far as methodology, with the appearance of traces related to sciences in the books of hadith tellers in central Maghreb.